At the crossroads: can desalination be a suitable public policy solution to address water scarcity in Chile's mining zones?. (15th March 2020) - Alvez, Amaya; Aitken, Douglas; Rivera, Diego; Vergara, Marcelo; McIntyre, Neil; Concha, Fernando
Abstract: Water scarcity is a global issue that is threatening social and economic development. One approach to alleviating scarcity is the incorporation of new water sources into supply systems, including desalinated seawater for industrial and municipal use. In Chile, large volumes of water are used in water-scarce regions where mining takes place, alongside agriculture and small communities. This situation has driven a debate around policies to increase the use of seawater to satisfy the water demand of the mining industry. The economic, social and environmental implications of such a policy, however, are poorly understood and the current regulatory framework to address concerns and uncertainties is inadequate. This paper presents a technical, legal, economic and environmental appraisal of such a policy and considers options to improve outcomes. The appraisal suggests that clear regulations derived from economic, social and environmental analysis must be generated to provide legal certainty and reduce risks. Alternative or complementary water supply options should be allowed where mining operations can demonstrate negligible hydrological and social impacts or use innovative solutions such as stakeholder water rights swaps and water efficiency technologies. We provide insight that will help to drive a better policymaking process aimed at tackling water scarcity in Chile and in similar areas of the world. Highlights: In Chile there is a drive to mandate seawater use in mining. The implications of such a policy are poorly understood. There are regulatory gaps that are causing widespread uncertainty. The economic, environmental and social trade-offs could be damaging. Further analysis and a more pragmatic approach is required that accounts for context.